1997
DOI: 10.1074/jbc.272.11.7062
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cytoplasmic Motifs Required for Short Prolactin Receptor Internalization

Abstract: Cloning of rat prolactin receptor (PRLR) cDNAs revealed the existence of two isoforms, termed short and long according to the length of their cytoplasmic domain. Internalization studies show, first, that PRLR internalization is hormone-dependent and, second, that ligand-receptor complexes of the short PRLR are internalized to a larger extent compared to the long form. In order to identify regions within the cytoplasmic domain of the short PRLR required for efficient internalization, serial truncations of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 54 publications
1
22
0
Order By: Relevance
“…Interestingly, successive deletions of these regions lead to a decrease in endocytosis, suggesting that normal endocytosis involves several motifs along the cytosolic tail and not only one specific short sequence as described for other receptors (12). The role of various cytosolic regions in endocytosis has been described previously for receptors such as the P-selectin (26), the prolactin receptor (27), and is also found in the IL2R␤ chain (28). The cytosolic domains of many membrane proteins have short sequences, usually including a tyrosine or a di-leucine motif, which mediate their rapid internalization through clathrincoated pits.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, successive deletions of these regions lead to a decrease in endocytosis, suggesting that normal endocytosis involves several motifs along the cytosolic tail and not only one specific short sequence as described for other receptors (12). The role of various cytosolic regions in endocytosis has been described previously for receptors such as the P-selectin (26), the prolactin receptor (27), and is also found in the IL2R␤ chain (28). The cytosolic domains of many membrane proteins have short sequences, usually including a tyrosine or a di-leucine motif, which mediate their rapid internalization through clathrincoated pits.…”
Section: Discussionmentioning
confidence: 98%
“…Differences in PRLactivated signaling pathways (3,4) and endocytic motifs among the alternatively spliced PRLR isoforms (7,9) suggest that post-ligand trafficking of the short isoforms will be distinct from the lPRLR. Understanding these processes, their regulation, and their interrelationships with signaling cascades in different target cells will increase our knowledge of PRL actions in physiologic activities and provide the basis to modulate its actions in pathological conditions, including breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Ligand binding to the lPRLR initiates internalization (6 -8), which is dynamin-dependent and is at least partially mediated by clathrin in a COS-7 cell model (7). Several cytoplasmic motifs distinct for the lPRLR (7) and short isoforms (7,9) have been identified that are critical for this process. Although PRL has been observed to either up-or down-regulate its receptor in complex in vivo systems, exogenous PRL reduced receptor levels in more defined experimental systems in vitro, a process blocked by inhibitors of lysosomal function (for review, see Ref.…”
mentioning
confidence: 99%
“…At the same time, the downregulation of the intermediate and short forms of PRLR, which lack the ␤-TrCP2 recognition motif, may be regulated by other E3 ligases, or these forms may undergo endocytosis and degradation in a ubiquitin-independent manner. For example, multiple endocytosis motifs (including phenylalanine and dileucine motifs) were found to bring about internalization of short forms of PRLR as well as of truncation mutants of the long form (37,51). Since intermediate or short forms of human PRLR are either partially or entirely deficient in mediating the signal transduction pathways induced by PRL (30,42), it is expected that ␤-TrCP2-dependent control of stability of the long-form PRLR is important for regulating a complete repertoire of PRL signaling.…”
Section: Discussionmentioning
confidence: 99%